Aust J Gen Pract 2018
DOI: 10.31128/afp-08-17-4314
|View full text |Cite
|
Sign up to set email alerts
|

Australian bat lyssavirus

Abstract: AUSTRALIAN BAT LYSSAVIRUS (ABLV) is regarded as endemic in Australian bats. It is one of 14 known lyssavirus species 1 and causes human illness that is indistinguishable from classical rabies. It has resulted in three known human deaths in Australia since 1996. 2 All Australian bats have the potential to carry and transmit ABLV, and potentially risky human exposures to bats are common. Timely post-exposure prophylaxis (PEP) is critical to prevent ABLV disease. ABLV in bats ABLV was first identified in an encep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Screening of Australian bat populations has shown ABLV in five out of six bat families present, and widespread prevalence [ 9 ]. As such, all contact with bats should be considered a potential transmission event, and exposed individuals should receive post-exposure prophylaxis in the form of a rabies vaccine and hIG as these species are in the same lyssavirus phylogroup, and cross-reactivity is present [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Screening of Australian bat populations has shown ABLV in five out of six bat families present, and widespread prevalence [ 9 ]. As such, all contact with bats should be considered a potential transmission event, and exposed individuals should receive post-exposure prophylaxis in the form of a rabies vaccine and hIG as these species are in the same lyssavirus phylogroup, and cross-reactivity is present [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human exposure can occur through a bite or scratch from animals infected with rabies or other lyssavirus (Mahadevan et al, 2016 ). Although Australia is currently rabies‐free, bat lyssavirus has been identified in all four species of Australian fruit bats and one species of insectivorous microbat (Merritt et al, 2018 ). A study on bat handling habits in 185 UK bat carers showed that only 16.7% of them always wore gloves and 68.8% had been bitten by a bat previously (Morris et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…exposures to Australian bat lyssavirus (ABLV) were the result of human-initiated contact by professional or volunteer bat carers (McCall et al, 2000). ABLV infection could lead to sensorineural dysfunction that deteriorates into hyperactivity, hydrophobia, and convulsions, and progresses to death eventually (Merritt et al, 2018).…”
mentioning
confidence: 99%
“…As a result, testing of bats is biased towards those more likely to be infected, resulting in an overestimate of the prevalence of ABLV. However, it has been estimated that less than 1% of healthy, wild flying foxes (a type of large bat) and insectivorous bats and 5%–10% of sick, injured or orphaned bats in Queensland, Australia, are infected with ABLV (Field, 2004; McCall et al., 2000; Merritt et al., 2018; Warrilow et al., 2003). A recent publication reported that in 2017 in Australia, 28 bats (6.7% of all those tested) were found to have ABLV infection, and 19 of these were bats found in Queensland (Wildlife Health Australia, 2017).…”
Section: Introductionmentioning
confidence: 99%